Evaluation of dynamic properties of nano oil palm empty fruit bunch filler/epoxy composites - Saba, Naheed; Jawaid, Mohammad; Alothman, Othman Y.; Almutairi, Zeyad (Elsevier Editora, 2019)
Cured epoxy resins pretense a constraint for variety of advanced applications due to its notably poor thermal and dynamic (viscoelastic) properties, hence required to minimize their properties prior to their usage. The aim of the present study is to evaluate the effect of nano oil palm empty fruit bunch (OPEFB) fibers at different loadings (1%, 3% and 5%) on the dynamic mechanical properties through dynamic mechanical analysis (DMA) in terms of storage modulus E′, loss modulus E″ and glass transition temperature (Tg) of epoxy composites. Results explored that dynamic properties of the epoxy composites get improved remarkably by the incorporation of nano OPEFB to epoxy composites, while 3% loading displays marked decrease in damping factor with relative to pure epoxy composites and the rest. Overall we perceived that the 3% loading of nano OPEFB filler is the best and optimal to enhance dynamic mechanical properties and to modify the damping factor of the epoxy composites resulting in most promising light weight and thermally stable composite structural materials.